Implementasi Metode Pembelajaran Kooperatif Tipe STAD dalam Meningkatkan Sikap Toleransi dan Hasil Belajar Siswa - Mufidah, Nastiti; Kurniawan, Abdul Fatah (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
The purpose of this article is to find out how the role of the implementation of the STAD (Student Teams Achievements Divisions) cooperative learning method is to increase student tolerance. And whether the STAD Cooperative learning method can improve student learning outcomes, especially in Social Science subjects. This research method is Classroom Action Research (CAR). This research consisted of two cycles, and each cycle consisted of four stages, namely: planning, implementation, observation, and reflection. The subjects of this study consisted of 64 students of class VIII B and C at SMPN 02 Ponorogo. Data collection methods used include questionnaire data, observation sheet data and student worksheets. Based on the results of the study, it was obtained data that the results of the questionnaire related to student tolerance resulted in an increase of 48.44% in the comparison of Cycle I and Cycle II. This increase was also strengthened by data obtained from the results of the observation sheet related to the tolerance level of students which also showed an increase of 15.63%. Furthermore, the results of research related to the increase in learning outcomes obtained from student worksheets showed an increase of 31.25%. The conclusion of this study shows that the implementation of the STAD type cooperative learning method can increase students’ tolerance attitude, as evidenced by questionnaires and observation sheets, while an increase in student learning outcomes can be proven by student worksheets.